Effects of probiotic supplementation on related side effects after chemoradiotherapy in cancer patients - Lu, Yongkai; Luo, Xiaoqin; Yang, Di; Li, Yi; Gong, Tuotuo; Li, Binglin; Cheng, Jian; Chen, Ruijuan; Guo, Xin; Yuan, Wei (Frontiers in Oncology, 2022)
Objectives Chemotherapy and radiotherapy generally cause serious adverse side effects in cancer patients, thereby affecting subsequent treatment. Numerous studies have shown that taking probiotics is an option for preventing and treating these side effects. In this investigation, a meta-analysis of the effects of oral probiotics on side effects brought on by radiotherapy, chemotherapy, or chemoradiotherapy treatment will be carried out. Methods Two researchers independently and carefully reviewed all pertinent studies that were published before June 30, 2022 and were accessible on PubMed, Embase, Cochrane Library, and the Web of Science. Moreover, the Cochrane Collaboration’s Tool was used to evaluate the risk of bias. Utilizing Review Manager software version 5.4, data were retrieved from eligible studies to evaluate their merits and determine odds ratios (OR) and 95% confidence intervals (CIs) (RevMan 5.4). Results 2 097 patients from 16 randomized controlled trials were extracted, and standard meta-analysis methods were used to examine the data. Compared with the placebo groups, oral probiotics significantly reduced the side effects caused by radiotherapy and chemotherapy on various types of cancer, such as head and neck cancer, pelvic and abdominal cancer, breast cancer, lung cancer, etc. (OR: 0.31, 95% CI: 0.20 – 0.48; P < 0.005). Further analysis found that the incidence of diarrhea in patients with pelvic and abdominal cancers (OR: 0.32, 95% CI: 0.16 - 0.65; P < 0.005) and the frequency of oral mucositis in patients with head and neck tumors were also significantly lower (OR: 0.28, 95% CI: 0.18 - 0.43; P < 0.005) after the oral administration of probiotics. This suggests that probiotics have a positive influence on the treatment of side effects after chemoradiotherapy. Additionally, a funnel plot revealed that there was no significant publication bias in this study. Conclusions Probiotics may help to reduce the occurrence of cancer therapy-related side effects, especially oral mucositis in head and neck tumors and diarrhea in patients with pelvic and abdominal tumors. However, given the small number of clinical trials involved, additional randomized, double-blind, multicentric trials in a larger population are required. This paper may assist researchers in improving trial design in the selection of probiotic strains and selecting appropriate patients who may benefit from probiotic treatments.